Association between clinical outcomes and restless legs syndrome in Japanese patients with ulcerative colitis. (19th July 2022) - Kitakata, Shogo; Furukawa, Shinya; Miyake, Teruki; Shiraishi, Kana; Tange, Kazuhiro; Hashimoto, Yu; Yagi, Sen; Ninomiya, Tomoyuki; Suzuki, Seiyuu; Shibata, Naozumi; Murakami, Hidehiro; Ohashi, Katsuhisa; et al.
Summary: Restless legs syndrome (RLS) is a common sleep disorder in the Western population. The prevalence of restless legs syndrome in the Japanese population is 4.6%. Inflammatory and/or immune alteration might be associated with the development of restless legs syndrome. Ulcerative colitis is a chronic inflammatory bowel disease. Evidence regarding the association between ulcerative colitis and the prevalence of restless legs syndrome is limited. Herein, we investigated the association between clinical outcomes and the prevalence of restless legs syndrome in Japanese patients with ulcerative colitis. This was a cross‐sectional study using baseline data from a prospective cohort study. Subjects in this study were 273 patients with ulcerative colitis. The definition of restless legs syndrome was achieved using a self‐administered questionnaire based on the diagnostic criteria for restless legs syndrome in an epidemiological study approved by the Executive Committee of the International Restless Leg Syndrome Study Group in 2002. Clinical outcomes were clinical remission and mucosal healing. The association between clinical remission and mucosal healing and the prevalence of restless legs syndrome was assessed by multivariate logistic regression analyses. The percentage of clinical remission and mucosal healing was 58.4% and 63.1%, respectively. The prevalence of restless legs syndrome in this cohort was 4.7%. Clinical remission (adjusted odds ratio 0.23, 95% confidence interval 0.05–0.93) and mucosal healing (adjusted odds ratio 0.23, 95% confidence interval 0.05–0.90) were independently inversely associated with restless legs syndrome. No association between serum haemoglobin and restless legs syndrome was found. In conclusion, clinical remission and mucosal healing were independently and inversely associated with the prevalence of restless legs syndrome in Japanese patients with ulcerative colitis.